2016
DOI: 10.1055/s-0035-1569454
|View full text |Cite
|
Sign up to set email alerts
|

Ipragliflozin as an Initial Therapy in Drug Naïve Subjects with Type 2 Diabetes

Abstract: These results suggest that ipragliflozin has good glycemic efficacy as an initial therapy in subjects with T2DM, although certain adverse events or tolerability issues are concerned. It improves insulin sensitivity and may restore the impaired beta-cell function. However body weight reduction with ipragliflozin is not associated with its glycemic efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
15
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(20 citation statements)
references
References 28 publications
5
15
0
Order By: Relevance
“…Similar glycemic and non-glycemic efficacies were reported with other SGLT-2 inhibitors [68]. With the simple mechanism of discarding glucose into the urine, SGLT-2 inhibitors including canagliflozin were shown to ameliorate beta-cell function and insulin resistance [13, 69]. However, consistent with their mechanisms of action, they are associated with a higher incidence of certain adverse events including genital mycotic infections, urinary tract infections, osmotic diuretic-related adverse events, and volume depletion-related adverse events [10].…”
Section: Introductionmentioning
confidence: 79%
“…Similar glycemic and non-glycemic efficacies were reported with other SGLT-2 inhibitors [68]. With the simple mechanism of discarding glucose into the urine, SGLT-2 inhibitors including canagliflozin were shown to ameliorate beta-cell function and insulin resistance [13, 69]. However, consistent with their mechanisms of action, they are associated with a higher incidence of certain adverse events including genital mycotic infections, urinary tract infections, osmotic diuretic-related adverse events, and volume depletion-related adverse events [10].…”
Section: Introductionmentioning
confidence: 79%
“…Similar glycemic and non-glycemic efficacies were reported with other SGLT-2 inhibitors [8, 9]. Via the simple mechanism of discarding glucose into the urine (correcting glucotoxicity) [10], ipragliflozin was shown to ameliorate impaired beta-cell function and insulin resistance [11]. Furthermore, preliminary reports indicated that ipragliflozin could regulate free fatty acid (FFA) levels, which might consequently influence lipotoxicity and thereby affect beta-cell function [12].…”
Section: Introductionmentioning
confidence: 88%
“…SGLT2 inhibitors are currently used as add-on therapy to metformin or other drugs as part of dual or triple therapy. However, they could also be used as an alternative first-line option in patients with contraindications to or intolerance of metformin (see Kutoh et al [11] and the references therein).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations